Atmosphere Self-Rectification from Aerosols - Tsitskishvili, Marat S. (Journals of Georgian Geophysical Society, 2017)
“Self-rectification’s velocity”, dry "sedimentation" and "washing" by atmospheric sediments. For different climatic regions and seasons, the values of the developed parameter that is of great importance for ecologically sound atmospheric protection.